EFEKTIVITAS MIND MAPPING BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR GEOGRAFI KELAS X DI MAN 2 KEBUMEN TAHUN 2015 (Edu Geography, 2016)
The purpose of this study is to know the comparison of the learning result between the mind mapping have a has basis CTL and the conventional, to know whether the mind mapping have a has basis CTL helped students achieved a completeness in the learning result and to know students’ perspective about mind mapping have a has basis CTL. The population of this study is students of grade X  IIS MAN 2 Kebumen. The sampling technique used was the purposive sampling, with class X IIS 3 and X IIS 2  as the experimental and control class. The dependent variable in this study is the use of mind mapping have a has basis CTL, and the independent variable is the cognitive learning result. The technique of data analysis was using descriptive percentage analysis and t-test. The result of this study showed that the cognitive learning result of the experimental class is better than the control class. It is proved by the t-test in which tvalue >ttable (3.006 > 2.00), so the Ho is rejected. The percentage of the classical completeness is ≥ 75. The percentage for the experimental class is 88.2%, which is in the good category, while the control class is 51.5, which is in the low category. An average score obtained from the result of the students’ perspective questionnaires was 28, which is in the agree category. The conclusion of this study is that mind mapping have a has basis CTL is more effective to be used in the geography learning than the conventional learning in class X IIS MAN 2 Kebumen in the sub-bab hydrology cycle, water shore, and its usage.